Analysis of different tropospheric energies in the surroundings of the Bay of Bengal during different cyclonic periods - ALAM, M.D. MAHBUB; SHAFEE, SULTANA (MAUSAM, 1997)
ABSTRACT. Upper-air data of 0000 UTC for standard isobaric surfaces at surface, 850, 700, 500, 400, 300, 200, 150 and 100 hPa levels for the different cyclonic periods in the last decade were considered for study. The dry static energy, the latent heat energy, the moist static energy and the total energy and their vertical distribution were studied in the surroundings of the Bay of Bengal in relation to the movement of the cyclone and their ultimate landfall. The effects of different tropospheric energies considering the pressure as a vertical coordinate are discussed with the help of graphs.